1998
DOI: 10.1111/j.1468-3156.1998.tb00058.x
|View full text |Cite
|
Sign up to set email alerts
|

The Five Accomplishments: A Framework for Obtaining Customer Feedback in a Health Service Community Learning Disability Team

Abstract: This paper examines the usefulness of using the philosophy of normalisation and, in particular, O'Brien's (1992) Five Accomplishments as a basis for evaluating client satisfaction with a community-based health service learning disabilities team. It is based on a survey of a group of people with mild learning disabilities, using the Five Accomplishments as a framework for a semi-structured interview. Areas of client satisfaction and dissatisfaction are discussed in the context of the use of a value-based means … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…There were a number of limitations of the evaluation, the most obvious being the lack of input from individuals with a learning disability about the AOT. An earlier evaluation of the community learning disability service was based on the views of service users (Murray et al. 1998); however, the intellectual and communication difficulties of the majority of individuals referred to the AOT showed that a similar approach could not be used in the current study.…”
Section: Discussionmentioning
confidence: 92%
“…There were a number of limitations of the evaluation, the most obvious being the lack of input from individuals with a learning disability about the AOT. An earlier evaluation of the community learning disability service was based on the views of service users (Murray et al. 1998); however, the intellectual and communication difficulties of the majority of individuals referred to the AOT showed that a similar approach could not be used in the current study.…”
Section: Discussionmentioning
confidence: 92%
“…Based on a care ethical approach, unconditional care focuses on seeing the client as a person, implying that every person needs attention, trust and a feeling of freedom of choice. In this respect, the five accomplishments (Murray and Lakhani 1998 ) which constitute a value-based framework to provide support to people with ID can be helpful. For professionals to take into account three of these five aspects, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…choice, community presence, relationships, respect, and competence. Services for individuals with learning disabilities are increasingly being evaluated by these criteria (McGowan 1996;Murray et al 1998). The role of a professional working with clients with learning disabilities may therefore represent a balance between maintaining clients' behaviour within certain parameters (duty of care) and an obligation to make choices available to clients to the extent that they can make valid decisions (enabling choice).…”
Section: Enabling Client Choicementioning
confidence: 99%